Profil Penderita Hipertensi dengan Manifestasi Rongga Mulut di RSUD Abdoel Wahab Syahranie Samarinda Periode 2016-2020 - Apriana, Apriana; Yani, Sinar; Sawitri, Endang (Jurnal Kebidanan Mutiara Mahakam, 2024)
Background: Hypertension is a manifestation of multi-factor hemodynamic balance disorders. Many treatments for hypertension have been proven to be effective, but there are some side effects that can be experienced due to the use of antihypertensive drugs, one of which can occur in the oral cavity. Purpose: This research aims to investigate the profile of hypertensive patients with oral manifestations at Abdoel Wahab Sjahranie Regional Public Hospital, Samarinda, from 2016 to 2020. Method: This research employed descriptive observational the data were analyzed univariately using 45 secondary data in the form of medical records of hypertensive patients with oral manifestations. Results: The results showed that ages ranging from 18-24=0, 25-34=0, 35-44=9, 45-54=15, 55-64=16, 65-74=5, 75=0. Gender in male=27, female= 18. Education D3=3, S1=12, S2=2. Job not working=8, household head=6, PNS/POLRI/TNI=9, self-employed=16, farmer/fisherman/labor=1, retired=4, others=1. Antihypertensive drugs amlodipine=37, captopril = 5, furosemide=3. Hypertensive patients with oral manifestations xerostomia=0, gingival hyperplasia=8, lichenoid reaction=0, stomatitis=8, periodontitis=20, gingivitis=9. Treatment of scaling and root planning=36, mouthwash= 8. It was concluded that the majority were aged 55-64, in males, at Strata 1 tertiary education, self-employed occupations, antihypertensive drugs which were often taken amlodipine, in hypertensive patients with frequent manifestations of periodontitis, and the treatment of scaling and root planning.